Intra-arterial therapies for liver cancer: assessing tumor response. Issue 2 (1st February 2017) - Stroehl, Yasmin W.; Letzen, Brian S.; van Breugel, Johanna M. M.; Geschwind, Jean-Francois; Chapiro, Julius
ABSTRACT: Introduction: Intra-arterial therapies (IATs) play an integral role in the management of unresectable hepatocellular carcinoma and liver metastases. The ability to accurately assess tumor response to intra-arterial therapies is crucial for clinical management. Several one- and two-dimensional manual imaging-based response assessment techniques, based both on tumor size or enhancement, have shown to be highly subjective and merely surrogate for the actual tumor as a whole. Areas covered: Given the currently existing literature, we will discuss all available tumor assessment techniques and criteria for liver cancer with a strong emphasis on 3D quantitative imaging biomarkers of tumor response in this review. Expert commentary: The growing role of information technology in medicine has brought about the advent of software-assisted, segmentation-based assessment techniques that address the outstanding issues of a subjective reader and provide for more accurate assessment techniques for the locally treated lesions. Three-dimensional quantitative tumor assessment techniques are superior to one- and two-dimensional measurements. This allows for treatment alterations and more precise targeting, potentially resulting in improved patient outcome.